Unification of visual rhetoric within design elements in packaging design for SMEs in Malaysia / Safrina Muhammad Azmi - Muhammad Azmi, Safrina (2022)
Malaysia is still heading towards achieving as a developed nation as envisioned in 2020. Small and Medium Enterprises (SMEs) are known as the largest contributor to the country's economic growth (GDP) and can be used as a platform to promote Malaysia through its food products; envisioned for to be among the players in exporting food products to the global market. However, some SMEs still face difficulties in penetrating certain markets due to poor packaging and branding which is said to also reflect product quality. Packaging design has been significantly discussed for centuries and is recognized as one of the important components in the marketing industry. Food products must be equipped with good packaging design as part of their marketing strategy and as a national brand. Various products have been worked on for export to ASEAN markets; however, after examining various categories of high potential products, the scope of this study will only discuss and measure the packaging design of Keropok Lekor products. This study may be limited due to government policy, rule of law and legislation where some packaging design criteria and guidelines are bound to restrictions that have been outlined. Due to time constraints and high population density, data collection was only conducted in the Klang Valley where it is believed to have a sufficient population to represent the entire population of Malaysia. The objective of this study is to identify the relevance of visual rhetoric approach in packaging design as well as determine persuasive ways in visual rhetoric approach, then build a novel framework for new product development in order to improve product development process for food products from SMEs. This research was conducted using a mixed method where it is believed its ability to collect sufficient data to achieve its objectives is very accurate. Next, visual analysis was performed based on the validation of the analytical data and it has met the objectives of the study significantly. Conclusively, this study has identified important elements in the visual rhetoric approach as key factors in producing packaging design, and as a result, built a novel career framework for new product development for SMEs' food products referring to new product development (NPD) designed by Philip Kotler (1997) where it is believed to have confirmed all the hypotheses in this study.